430 Time restricted feeding in diet induced obesity mouse model reduces aortic stiffness and inflammatory T cells. (April 2022) - Edell, Claudia; Pati, Paramita; Colson, Jackson; Molina, Patrick; Pollock, David M; Pollock, Jennifer S
Abstract : OBJECTIVES/GOALS: Time restricted feeding (TRF) in diet induced obesity (DIO) has several health benefits, including improved metabolic rhythms and inflammation. Our lab has shown that TRF in DIO significantly reduces renal and aortic damage. The main goal of our research is to understand how TRF impacts aortic function, organ damage, and T cell activation in DIO. METHODS/STUDY POPULATION: We will use a 20-week DIO model, where mice will be on 20 weeks of normal fat diet (ND) or high fat diet (HFD). During weeks 18-20, mice will go through TRF intervention where food is restricted to the 12-hour active period or continue ad libitum feeding. At the end of the 2-week TRF intervention or continued ad libitum feeding, aortic stiffness will be measured via pulse wave velocity measurements. We will also collect kidney, aorta, and small intestine at the end of the 20-week protocol for flow cytometric analysis of tissue T cell activation as well as histological assessments. This will allow us to determine the relationship with organ damage, organ function, and the T cell response. We will also analyze tissue and circulating levels of inflammatory T cell-derived cytokines such as interleukin-17A (IL-17A) via ELISA. RESULTS/ANTICIPATED RESULTS: DIO mice showed significantly increased aortic stiffness (measured by pulse wave velocity) compared to mice on ND. Interestingly, TRF intervention in DIO mice reduced aortic stiffness compared to DIO ad libitum. Histological assessments also showed that TRF abolished aortic and kidney fibrosis suggesting a role for the timing of feeding in regulating aortic function and organ damage from chronic HFD. We have several ongoing experiments to determine the T cell response with TRF in DIO mice. We predict that TRF in DIO mice will significantly decrease inflammatory T cells and reduce cytokine abundance in target organs. DISCUSSION/SIGNIFICANCE: Our lab has shown that TRF reduces aortic thickness and aortic and kidney fibrosis, but the driving mechanisms are unknown. We propose that TRF reduces T cell activation in DIO mice leading to reduced organ damage. Our work will provide insight on how TRF in DIO regulates the T cell response and may improve inflammation in the kidney and aorta.